The evolution of the equatorial thermocline and the early Pliocene El Padre mean state. Issue 12 (18th June 2015) - Ford, Heather L.; Ravelo, A. Christina; Dekens, Petra S.; LaRiviere, Jonathan P.; Wara, Michael W.
Abstract The tropical Pacific thermocline strength, depth, and tilt are critical to tropical mean state and variability. During the early Pliocene (~3.5 to 4.5 Ma), the Eastern Equatorial Pacific (EEP) thermocline was deeper and the cold tongue was warmer than today, which resulted in a mean state with a reduced zonal sea surface temperature gradient or El Padre. However, it is unclear whether the deep thermocline was a local feature of the EEP or a basin‐wide condition with global implications. Our measurements of Mg/Ca of Globorotalia tumida in a western equatorial Pacific site indicate Pliocene subsurface temperatures warmer than today; thus, El Padre included a basin‐wide thermocline that was relatively warm, deep, and weakly tilted. At ~4 Ma, thermocline steepening was coupled to cooling of the cold tongue. Since ~4 Ma, the basin‐wide thermocline cooled/shoaled gradually, with implications for thermocline feedbacks in tropical dynamics and the interpretation of TEX86‐derived temperatures.